Mapping knowledge landscapes and emerging trends of sonodynamic therapy: A bibliometric and visualized study - Wu, Zhenjiang; Cheng, Kunming; Shen, Zefeng; Lu, Yanqiu; Wang, Hongtao; Wang, Guolei; Wang, Yulin; Yang, Weiguang; Sun, Zaijie; Guo, Qiang; Wu, Haiyang (Frontiers in Pharmacology, 2023)
Background: Ultrasound-triggered sonodynamic therapy (SDT), as a non-invasive approach, has attracted considerable attention in a wide variety of malignant tumors and other diseases. Over the past 2 decades, the number of scientific publications on SDT has increased rapidly. However, there is still a lack of one comprehensive report that summarizes the global research trends and knowledge landscapes in the field of SDT in detail. Thus, we performed a bibliometric analysis on SDT from 2000 to 2021 to track the current hotspots and highlight future directions. Methods: We collected publications on SDT research from the Web of Science Core Collection database. The annual number of publications and citations, major contributors, popular journals, international collaborations, co-cited references and co-occurrence keywords were analyzed and visualized with CiteSpace, VOSviewer, and R-bibliometrix. Results: A total of 701 publications were included. The annual publication output increased from 5 in 2000 to 175 in 2021, and the average growth rate was 18.4%. China was the most productive country with 463 documents (66.05%), and Harbin Medical University was the most prolific institution (N = 73). Ultrasound in Medicine and Biology published the most papers related to SDT. Materials Science, and Chemistry were the research areas receiving the most interest. All the keywords were divided into four different clusters including studies on mechanisms, studies on drug delivery and nanoparticles, studies on cancer therapy, as well as studies on ultrasound and sonosensitizers. In addition to nanomaterials-related studies including nanoparticles, mesoporous silica nanoparticles, nanosheets, liposomes, microbubble and TiO2 nanoparticle, the following research directions such as immunogenic cell death, metal-organic framework, photothermal therapy, hypoxia, tumor microenvironment, chemodynamic therapy, combination therapy, tumor resistance, intensity focused ultrasound, drug delivery, and Staphylococcus aureus also deserve further attention and may continue to explode in the future. Conclusion: SDT has a bright future in the field of cancer treatment, and nanomaterials have increasingly influenced the SDT field with the development of nano-technology. Overall, this comprehensive bibliometric study was the first attempt to analyze the field of SDT, which could provide valuable references for later researchers to better understand the global research trends, hotspots and frontiers in this domain.